Study of Chromatographic Retention in Phosphate Solution on the Basis of Linear Solvation Energy Relationships - Han, D.D.; Row, K.H. (Asian Journal of Chemistry, 2010)
Two kinds of phosphates i.e., sodium dihydrogen phosphate (NaH2PO4) and disodium hydrogen phosphate (Na2HPO4) were used as additives in linear solvation energy relationships (LSER) model to investigate the fundamental chemical interactions governing the retentions of 7 aromatic compounds. The effects of different concentrations of the buffer and modifier on the retentions were discussed by using acetonitrile/water (v/v) mobile phases on a C18 column. Linear solvation energy relationships model demonstrated high potential to predict retention factors with very high correlation coefficients (r2 > 0.99 in NaH2PO4 and r2 > 0.96 in Na2HPO4). A comparison of predicted and experimental retention factors suggests that LSER formalism is able to reproduce the experimental retention factors of the solutes studied in the different experimental conditions adequately.